Improvement in oxidation resistance and electrical properties of SOFCs interconnect via annealing of spinel layer - Hassan, Muhammad Aqib (2021)
Modernization in power generation system have introduced green technology which include fuel cells; Solid oxide fuel cell (SOFC) is the latest technology.